2014
DOI: 10.1177/1469605314522897
|View full text |Cite
|
Sign up to set email alerts
|

Before the flood: Loss of place, mnemonics, and ‘resources’ ahead of the Metolong Dam, Lesotho

Abstract: Natural resource extraction projects such as dams and mines entail alteration to or destruction of natural and cultural landscapes. Heritage mitigation efforts often propose compensating for or salvaging material heritage, largely because this can be inventoried and evaluated alongside economic and environmental resources. Intangible Cultural Heritage (ICH) is often overlooked, despite the fact that tangibles, intangibles, and economic resources together constitute the impacted landscape. Writing from the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Ntloana Tšoana offered a relatively well-hidden location with easily defendable access routes down the steep slopes and across the river, yet was also eminently habitable and could support a significant number of people and cattle on its flat, riverside terrace. The current traditional leader of the village on the opposite side of the river, Ha Makhale, still uses Ntloana Tšoana for the production of powerful magic, a practice which involves grinding various ingredients in the cupules at the front of the site, something she traced back to her great-grandfather's initial occupation and the casting of protective spells (King & Nic Eoin 2014). Other supernatural associations relate to the koetsa just twenty metres upstream, thought by some to be the home of a Noha-eametsi, yet also used by the Zionist church today for baptism ceremonies.…”
Section: Introducing Ntloana Tšoanamentioning
confidence: 99%
“…Ntloana Tšoana offered a relatively well-hidden location with easily defendable access routes down the steep slopes and across the river, yet was also eminently habitable and could support a significant number of people and cattle on its flat, riverside terrace. The current traditional leader of the village on the opposite side of the river, Ha Makhale, still uses Ntloana Tšoana for the production of powerful magic, a practice which involves grinding various ingredients in the cupules at the front of the site, something she traced back to her great-grandfather's initial occupation and the casting of protective spells (King & Nic Eoin 2014). Other supernatural associations relate to the koetsa just twenty metres upstream, thought by some to be the home of a Noha-eametsi, yet also used by the Zionist church today for baptism ceremonies.…”
Section: Introducing Ntloana Tšoanamentioning
confidence: 99%
“…Relict mining landscapes can be viewed as cemeteries of a dead industrial past – of toil, burden and sacrifice. Reshaping of the land surface by the process and by-products of mining gives rise to a ‘non-natural’ landscape, one that has a complex relationship with individual and collective cultural identity (Storm and Olsson, 2013; Summerby-Murray, 2007), degree of landscape change and ‘landscape memory’ (Skaloš and Kašparová, 2012; Wheeler, 2014), and metal-containing rocks as an emblem of the ‘more-than-human’ world of elemental Earth forces (Gibbs, 2009; King and Nic Eoin, 2014; Salas Carreño, 2017). As such, mining landscapes have similar physical and non-physical properties to formal cemeteries and grave sites.…”
Section: Discussionmentioning
confidence: 99%
“…These included health awareness programmes, livelihood income generating projects, financial compensation for loss of assets and resources, job creation, construction of health and communication infrastructure (SMEC, 2008). Reviewed documents showed that Metolong Dam project led to development of social amenities such as foot bridges and a tarred access road of 32km road to the site were constructed across Phuthiatsana River linking communities either side of the dam, making movement of goods and people to and from the communities easier (King and Coin, 2014).…”
Section: Mainstreaming Of Hia Recommendations In Metolong In Post Dam Constructionmentioning
confidence: 99%